Chemical fractionation and mobility of metals in floodplain soils of the lower reaches of the River Niger, Nigeria. Issue 1 (2nd January 2018) - Iwegbue, Chukwujindu M.A.; Tesi, Godswill O.; Overah, Loretta C.; Nwajei, Godwin E.; Martincigh, Bice S.
Abstract : The chemical fractionation of nine metals, Cd, Pb, Cr, Ni, Cu, Co, Ba, Mn and Zn, in soil profiles of the floodplain of the lower reaches of the River Niger in Nigeria, was investigated with a view to providing information on the forms, bioavailability and mobility of these metals in the soil profiles. The chemical forms of metals in the soil were determined by using the European Community Bureau of Reference (BCR) sequential chemical extraction method and the concentrations were measured by inductively coupled plasma-atomic emission spectrophotometry (ICP-AES). The results indicated that the residual and Fe-Mn oxide/hydroxide phases were the predominant forms of the metals in the soil profiles. The percentage of metals in the readily available and potentially available fractions followed the order: Pb > Ba > Cd > Ni > Co > Zn > Mn > Cu > Cr. Significant proportions of these metals were found in the potentially available phases, which indicate an increase in mobility and availability as a result of changes in the physicochemical characteristics (pH and Eh) of the soil following flooding events.